Skin Barrier Function and Infant Tidal Flow-Volume Loops-A Population-Based Observational Study - Martin Färdig; Hrefna Katrín Gudmundsdóttir; Angela Hoyer; Karen Eline Stensby Bains; Catarina Almqvist; Christine Monceyron Jonassen; Eva Maria Rehbinder; Håvard O. Skjerven; Anne Cathrine Staff; Riyas Vettukattil; Cilla Söderhäll; Karin C. Lødrup Carlsen; et al. (MDPI AG, 2022)
Background: The relationship between the skin barrier- and lung function in infancy is largely unexplored. We aimed to explore if reduced skin barrier function by high transepidermal water loss (TEWL), or manifestations of eczema or Filaggrin (FLG) mutations, were associated with lower lung function in three-month-old infants. Methods: From the population-based PreventADALL cohort, 899 infants with lung function measurements and information on either TEWL, eczema at three months of age and/or FLG mutations were included. Lower lung function by tidal flow-volume loops was defined as a ratio of time to peak tidal expiratory flow to expiratory time (tPTEF/tE) <0.25 and a tPTEF <0.17 s (<25th percentile). A high TEWL >8.83 g/m2/h (>75th percentile) denoted reduced skin barrier function, and DNA was genotyped for FLG mutations (R501X, 2282del4 and R2447X). Results: Neither a high TEWL, nor eczema or FLG mutations, were associated with a lower tPTEF/tE. While a high TEWL was associated with a lower tPTEF; adjusted OR (95% CI) 1.61 (1.08, 2.42), the presence of eczema or FLG mutations were not. Conclusions: Overall, a high TEWL, eczema or FLG mutations were not associated with lower lung function in healthy three-month-old infants. However, an inverse association between high TEWL and tPTEF was observed, indicating a possible link between the skin barrier- and lung function in early infancy.